Radiation effect in normal tissue - Dörr, W. (Nuklearmedizin - NuclearMedicine, 2010)
The curative effectivity of external or internal radiotherapy necessitates exposure of normal tissues with significant radiation doses, and hence must be associated with an accepted rate of side effects. These complications can not a priori be considered as an indication of a too aggressive therapy. Based on the time of first diagnosis, early (acute) and late (chronic) radiation sequelae in normal tissues can be distinguished. Early reactions per definition occur within 90 days after onset of the radiation exposure. They are based on impairment of cell production in turnover tissues, which in face of ongoing cell loss results in hypoplasia and eventually a complete loss of functional cells. The latent time is largely independent of dose and is defined by tissue biology (turnover time). Usually, complete healing of early reactions is observed. Late radiation effects can occur after symptom-free latent times of months to many years, with an inverse dependence of latency on dose. Late normal tissue changes are progressive and usually irreversible. They are based on a complex interaction of damage to various cell populations (organ parenchyma, connective tissue, capillaries), with a contribution from macrophages. Late effects are sensitive for a reduction in dose rate (recovery effects).A number of biologically based strategies for protection of normal tissues or for amelioration of radiation effects was and still is tested in experimental systems, yet, only a small fraction of these approaches has so far been introduced into clinical studies. One advantage of most of the methods is that they may be effective even if the treatment starts way after the end of radiation exposure. For a clinical exploitation, hence, the availability of early indicators for the progression of subclinical damage in the individual patient would be desirable. Moreover, there is need to further investigate the molecular pathogenesis of normal tissue effects in more detail, in order to optimise biology based preventive strategies, as well as to identify the precise mechanisms of already tested approaches (e. g. stem cells).
Keywords: Normal tissue; pathogenesis; factors of radiation sensitivity; protection